Expo 86, Vancouver, B.C., Canada - the CP Air Skyride - Jurgen Vogt/Photo Graphics::::::::: (Agency Press)
The CP Air Skyride passes over the Northwest Territories Pavilion as it travels from the Pavilion of Promise in the Red Zone to Folklife in the Purple Zone.